Some Factors Affecting the Defense-Security in Central Highland Region Today - Nguyen Van Tan (International Journal of Science and Society, 2020)
The Central Highlands region is strategically important locations on national defense and security. Currently, there are many objective and subjective factors that have been affecting the strengthening and establishment of national defense - security in particular, development and international integration in this area in general. The article focuses on clarifying a number of factors that have been directly and generator affecting the assurance of national defense and security in the Central Highlands today.